H influenzae LPS colocalization with Toll-like receptor 4 in eosinophilic esophagitis - Ravi, Anupama; Marietta, Eric V.; Alexander, Jeffrey A.; Murray, Joseph A.; Katzka, David A. (The journal of allergy and clinical immunology. Global, 2023)
Patients with eosinophilic esophagitis (EoE) have a unique esophageal microbiome with increased presence of Haemophilus influenzae, but its role in the disease is unclear. Microbiome-derived bacterial LPS activation of Toll-like receptors (TLR) is a potential mechanism for inducing inflammation in other chronic inflammatory diseases, but it has not been studied in EoE. Our aim was therefore to study microbiome-derived bacterial LPS activation of TLRs in EoE. We studied 10 patients with active EoE, 9 patients with inactive EoE, and 10 control patients. Esophageal biopsy samples from the controls, patients with active EoE (>15 eosinophils/hpf), and patients with inactive EoE were immunostained for the presence of H influenzae LPS, presence of TLR4, and colocalization of LPS and TLR4. Staining intensity was measured by using confocal laser microscopy and scored on a scale from 0 to 3 as the average score assigned by 2 blinded observers. H influenzae LPS was detected by positive staining in 20 of the 29 patients (69.0%), including 9 of the 10 patients with active EoE (90.0%), 8 of the 9 patients with inactive EoE (89.9%), and 3 of the 10 controls (30%); its level was greater in the patients with active EoE than in the controls (P = .063). TLR4 was detected by positive staining in 19 of the 29 patients (65.5%), including 9 of the 10 patients with active EoE (90.0%), 4 of the 9 patients with inactive EoE (44.4%), and 6 of the 10 controls (60.0%); its level was higher in the patients with active EoE than in those with inactive EoE (P = .096). The result of testing for colocalization of LPS and TLR4 was positive in 8 of 10 patients with active EoE (80.0%), 1 of 9 patients with inactive EoE (11.1%), and 1 of 10 control patients (10.0%), with greater colocalization of H influenzae LPS and TLR4 staining density in the samples from patients with active EoE than in the controls or the patients with inactive EoE (P = .009 and P = .018, respectively). Esophageal microbiome–rich H influenzae LPS colocalizes to TLR4 in active EoE. These data lend further support to a role for the esophageal microbiome in modulating the activity of EoE.